Pengembangan Media Pembelajaran Powerpoint pada Matepelajaran Matematika dengan Materi Bangun Datar untuk Siswa Kelas IV Sekolah Dasar - Saputri, Aprinda Ageng; Ain, Siti Quratul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The world's IT sector is no exception with Indonesia experiencing rapid development despite the Covid 19 pandemic, where the world of education is required to use and utilize a technology called computers. The study held below has a goal of developing media or materials used in the implementation of mathematics learning activities, especially in learning flat shapes using animation on the Microsoft Point application which is applied to grade IV (six) elementary school (SD) students. The purpose of this research is to examine the truth and readiness of the media or tools used in the implementation of mathematics learning activities, especially in learning to build flat using animations contained in the Microsoft PowerPoint application. The method used in this study is a quantitative method with a Research & Development (R&D) approach. This technique focuses on developing ADDIE through several stages, including (1) Analysis, (2) Designing, and (3) Development. Then 6 experts will test the validity, where this test will be divided into testing on design, language testing, and material testing, each of which requires at least 2 experts in their fields. The tool used in this study is the expert validation sheet. The results of this study are in the form of videos containing mathematics learning, especially in the fourth (sixth) grade flat shape learning. The animations contained in the Microsoft PowerPoint application were developed in the form of learning videos. The conclusion in the study of developing the media or tools used in this mathematics learning activity is in the "very valid" and "appropriate" categories. The initial validation carried out by this expert got 73.33% results so it was in the feasible category. Meanwhile, for the second validation, it got 92. 5% so that it is in the very feasible category. Then the validation in the language field for the first time got 72.91% results and placed it in the proper category, while for the second validation it got 91.6% results so it was in the very feasible category, then the last validation in the material field for the first time got 76.56% results so that it was in the proper category and for the second time validation it got 95.31% results so it was in the very feasible category.